Yemen Social Accounting Matrix, 2012 - International Food Policy Research Institute; Ministry of Planning and International Cooperation, Government of Yemen; Kiel Institute for the World Economy (International Food Policy Research Institute, 2014)
This data study includes Yemen Social Accounting Matrix (SAM) for the year 2012. The national SAM is built using the 2012 national accounts, government budgets, balance of payments, and 2007 input-output tables. It provides a detailed representation of Yemen economy. It separates 24 activities and commodities; 10 agricultural sectors, fisheries and forestry, 2 for mining, 4 for manufacturing, 1 for electricity,water, construction and trade and transport, and 3 service sectors. Information on labor is drawn from 2005/06 household budget survey (HBS) and dis-aggregates labor into three categories: unskilled, semi-skilled and skilled. Finally the SAM identifies government investments and foreign accounts. Therefore, this database can be a very good input for undertaking economy wide impact assessments, SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.